PELATIHAN PERSAMAAN DASAR AKUNTANSI DALAM KEGIATAN MBKM DI SMK YP IPPI PETOJO - Fahrulroji, Maulida Muthokharoh; Susanto, Liana (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2024)
Merdeka Belajar Kampus Merdeka (MBKM) is an innovation created by the Ministry of Education, Culture and Research and Technology and states a policy for changing the higher education system in Indonesia to produce more relevant graduates and aims to encourage students to master various sciences to prepare for entering the world of work. MBKM has eight programs, one of which is teaching assistance in the education unit. This Teaching Assistance MBKM will be held specifically for students of YP IPPI Petojo Vocational School. Implementation of the MBKM program will involve conveying information directly to students in the form of face-to-face meetings. The time period for implementing the MBKM program starts from August to October 2023. During the teaching period students apply their knowledge to YP IPPI Petojo Vocational School students. This MBKM activity began with an initial meeting between the school and Tarumanagara University to identify the school's needs and interests regarding this collaboration. After getting positive responses, we concluded that the theme we had chosen was the basic accounting equation which includes assets, debt and capital. The results resulting from this activity include MBKM publications and reporting. Publication is the final stage in the MBKM program, we submit a report on the results of this activity to the publication institute at Tarumanagara University as a form of responsibility.